PENGARUH PENERAPAN MODIFIKASI PERMAINAN TERHADAP EFEKTIVITAS PEMBELAJARAN TOLAK PELURU STUDI PADA SISWA KELAS V SDN WONOPLINTAHAN I/276 PRAMBON KABUPATEN SIDOARJO - SULTONI, IMAM (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Shot put is one of athletics are easy to do and achieve but  need good learning of effectiveness especially for  elementary school students. Learning effectiveness is often overlooked, despite the fact that is very important in the learning process. the effectiveness of learning  to be a measurement of educational success in learning process, if the learning process is effective then the goal will be achieved . Learning effectiveness can be created through how to teach methods. A good learning of effectiveness in the shot put educators can use a modified game that make students will be more active in learning process and learning  environment that are not too rigid or monotonic. The method that are used here is the pretest and posttest. The design of it is “One Group Pretest - Posttest Design” and instruments were used are : (1). Class Observation Sheet Dikjasor, it is a sheet that contains an observations that are used for comparison between pretest and posttest at the learning  process. (2). FCE Questionnaire (Formative Class Evaluation) is used to determine the opinion of  the students towards learning process.(3). Rubric Assessment Mastery Learning is used to determine learning process result in learning student mastery. Based on SPSS data processing results in research of 24 students is known that α (0.05) Z value is -3,684b  and with Asypm. Sig. ( 2-tailed ) ,000. This is indicates there is a difference if Sig < α (0.05) then it means the received  is effect of using games in learning effectiveness modification shot put with an increased amount of learning that is 9.46 % . Conclusions of this study shows that Sig < α (0.05) then acceptable  can be concluded that the application of Learning Effectiveness Shot Put At Elementary School Fifth Grade Students Wonoplintahan I/276 Prambon Sidoarjo With Modification Game are effective in the shot-put learning and improve student learning result. Keywords : Modification Games, Effectiveness Learning Shot Put